Effect of Moringa Oleifera (Moringa) leaf extract on the shelf life of smoked (Oreochromis niloticus) Tilapia fish using an improved traditional kiln - Abdulkareem, A. A; Gana, E. S; Agbo, A. N. (ADAN JOURNAL OF AGRICULTURE, 2026)
This study evaluated the effect of Moringa oleifera leaf extract on the shelf-life and quality of smoked Oreochromis niloticus (tilapia) processed using an improved traditional smoking kiln. Tilapia samples were treated with varying concentrations of aqueous Moringa oleifera extract (16, 19, and 21 mg/L) prior to smoking. Proximate composition and microbial load analyses were conducted bi-weekly over two months to assess the impact of treatment on moisture, protein, lipid, ash content, and microbial contamination. Results showed a significant decrease in moisture and lipid content and an increase in protein and ash concentration with increasing Moringa extract levels. Microbial analyses indicated dose-dependent reductions in major bacterial populations including Staphylococcus spp., Bacillus spp., Escherichia coli, and fungi such as Aspergillus niger on treated samples compared to controls. Despite these reductions, microbial counts remained relatively high, suggesting the need for improved hygiene and complementary preservation strategies. The findings demonstrate that Moringa oleifera leaf extract effectively enhances smoked tilapia’s shelf-life by inhibiting microbial growth and improving nutritional quality when used in conjunction with an improved smoking kiln. This approach offers a sustainable, natural lternative to synthetic preservatives for fish processors, potentially reducing post-harvest losses and supporting food security in resource-limited settings